Development of Scientific Problem-Solving Skills in 5th Grader Using Problem-Based Learning - Pimporn Pinyo; Chaiphat Plybour; Orrasa Prasitnok (Journal of Educational Issues, 2024)
The purpose of the research was to develop scientific problem-solving thinking skills in fifth-grade pupils by using problem-based learning (PBL). The target group was 21 pupils attending a primary school located in Sakon Nakhon province, northeast Thailand. Data were collected twice (first and second cycle) in substance change learning unit in the second semester of 2021 academic year. Three types of research tools were the following: six PBL plans within 12 hours (pupils experienced 3 plans in each cycle and 2 hours for each plan), scientific problem-solving thinking skill test (SPSTST), and observation of scientific problem-solving behavior (OSPSB). A minimum criterion was 70% of mean score in SPSTST and SPSBO, and at least 70% of the pupils reached that. The results in the 1st cycle showed that pupils had 67.46% in SPSTST and 57.14% of them passed the minimum criterion. They had 65.85% in SPSBO and 57.14% of them passed the minimum criterion. In the 2nd cycle, pupils had 91.67% in SPSTST and 90.48% of them met the minimum criterion. They had 87.58% in SPSBO and 90.48% of them met the minimum criterion.